1999
DOI: 10.1039/a806921b
|View full text |Cite
|
Sign up to set email alerts
|

Optical biosensing of nitric oxide using the metalloprotein cytochrome c′

Abstract: The metalloprotein cytochrome c' was extracted and purified from the bacterium Paracoccus denitrificans in order to develop a specific biosensing system for nitric oxide (NO). The metalloprotein was encapsulated in a porous silicate sol-gel glass to enable spectroscopic changes in the haem centre as a function of NO ligation to be quantified using absorption measurements. Spectroscopic evidence suggested that, between 2 and 4 d after encapsulation, the cytochrome c' protein changed conformation in the locality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Indeed, it was shown that enzymes retain their activity toward their target and antibodies are able to bind their corresponding antigen . These interesting properties triggered the development of biosensors for medical or environmental diagnosis using metalloproteins , enzymes , or antibodies entrapped in silica gels.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it was shown that enzymes retain their activity toward their target and antibodies are able to bind their corresponding antigen . These interesting properties triggered the development of biosensors for medical or environmental diagnosis using metalloproteins , enzymes , or antibodies entrapped in silica gels.…”
Section: Introductionmentioning
confidence: 99%
“…The physical entrapment of molecules using the solgel process [10,11] has been used for the development of NO electrochemical and optical sensors. Sensors entrapped in gels offer numerous advantages when compared with liquid based systems: they are easier to manipulate, allow species detection and concentrations measurements with less contamination of the sample, can be used for continuous sensing and are normally more stable.…”
Section: Introductionmentioning
confidence: 99%
“…We are interested in developing optical biosensors and in this article report the use of cytochrome c , as the biological sensing molecule, deposited onto ITO electrodes for the optical detection of NO. Previously we have encapsulated cytochrome c , and another heme protein, cytochrome c ‘, within silica sol−gel matrixes for the measurement of NO. Such biosensing measurements relied on the use of chemical reductants and oxidants to regenerate the heme center for multiple use.…”
Section: Introductionmentioning
confidence: 99%